Analysis of Financial Performance Ratio of Medan City Government 2020 – 2023 - Pitaloka, Allika Ayu Diah; Syahputri, Cindy; Anggreani, Nabilla Puteri; Indriani, Sela; Chrisna, Heriyati (Lembaga Riset Mutiara Akbar, 2024)
Financial performance measurement is very necessary to assess regional government accountability in financial management. Accountability is not only about the ability to demonstrate the use of public money, but also includes the ability to prove that such use was carried out efficiently, effectively and economically. Currently, the Medan City Government is facing problems related to the percentage of PAD achieved from 2020 to 2023. This research aims to analyze the financial performance of the City of Medan using Regional Financial Independence Ratio Analysis, PAD Effectiveness Ratio, PAD Efficiency Ratio, Degree of Decentralization Ratio, Growth Ratio, and Conformity Ratio in the 2020-2023 period. The method used is quantitative descriptive, namely calculating financial data obtained to solve problems by analyzing various ratios. The findings of this research show that the financial performance of the Medan City Government is quite good in terms of independence, in the